Smart Health Village berbasis Web sebagai Media Informasi Kejadian Bencana - Hastuti, Apriyani Puji; Roesardhyati, Ratna; Kurniawan, Ardhiles Wahyu; Ambarika, Rahmania; Pradini, Risqy Siwi (Penerbit Goodwood, 2024)
Purpose: The aim of community services was to socialize and inform Balakarcana officers to report information about disaster events. Disaster-prone areas have the potential for natural disasters such as earthquakes, mountain eruptions, and landslides caused by activity or movement from the bottom of the earth. Understanding the potential for natural disasters in each region is an anticipatory step toward minimizing the number of victims of natural disasters. Precise and accurate information is required for disaster management. The community also experiences difficulties in receiving information and submitting reports on the village conditions. In this community service activity, a web-based smart health village application was developed so that it could be accessed by all residents of the local area. Methodology: The method of implementing this activity consists of the design stage, application creation, system design, outreach and training, and trial reporting of information on disaster events based on the smart health village concept in the Poncokusumo Region, Malang Regency, from July to October 2023. Results: This service is an application system for reporting information on disaster events to increase community preparedness for disasters. This web-based application system allows the community (users), admins (task force), and verifiers (village officials) to access anywhere and at any time, thereby increasing the capability and quality of human resources in disaster preparedness and disaster-prone areas. Limitations: People who do not have Internet access experience difficulties in receiving information and submitting reports regarding village conditions. Contribution: Utilization of web-based information systems to make it easier for village officials to validate disaster events and as an effort to improve disaster preparedness.